The teacher wars : a history of America's most embattled profession - Goldstein, Dana (Doubleday, 2014)
"A brilliant young scholar's history of 175 years of teaching in America shows that teachers have always borne the brunt of shifting, often impossible expectations. In other nations, public schools are one thread in a quilt that includes free universal child care, health care, and job training. Here, schools are the whole cloth. Today we look around the world at countries like Finland and South Korea, whose students consistently outscore Americans on standardized tests, and wonder what we are doing wrong. Dana Goldstein first asks the often-forgotten question: "How did we get here?" She argues that we must take the historical perspective, understanding the political and cultural baggage that is tied to teaching, if we have any hope of positive change. In her lively, character-driven history of public teaching, Goldstein guides us through American education's many passages, including the feminization of teaching in the 1800s and the fateful growth of unions, and shows that the battles fought over nearly two centuries echo the very dilemmas we cope with today. Goldstein shows that recent innovations like Teach for America, merit pay, and teacher evaluation via student testing are actually as old as public schools themselves. Goldstein argues that long-festering ambivalence about teachers--are they civil servants or academic professionals?--and unrealistic expectations that the schools alone should compensate for poverty's ills have driven the most ambitious people from becoming teachers and sticking with it. In America's past, and in local innovations that promote the professionalization of the teaching corps, Goldstein finds answers to an age-old problem"--